2019
DOI: 10.1186/s12889-019-6641-4
|View full text |Cite
|
Sign up to set email alerts
|

30 years of fatal dengue cases in Brazil: a review

Abstract: BackgroundOver the last 30 years, extensive dengue epidemics have occurred in Brazil, characterized by emergences and re-emergences of different serotypes, a change in the epidemiological profile and an increase in the number of severe and fatal cases. Here, we present a review on the dengue fatal cases that occurred in Brazil in 30 years (1986–2015).MethodsWe performed an ecological study by using secondary data on dengue fatal cases obtained in the National System of Reported Diseases (Sistema de Informação … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 50 publications
6
58
0
10
Order By: Relevance
“…There is evidence that women usually seek health care assistance more frequently, not necessarily meaning that they are more affected by diseases, but, instead, that they tend to be more careful with their own wellness [64,65]. In Brazil, some studies found higher dengue notification among women [66,67], and others showed no significant sex difference [68,69]. In our data, from 2007 to 2015, 55% of patients that notified DENV cases were women while 45% were men, while the 2010 Population Census indicates that 52% of the residents in Campinas were women, and 48% were men [20].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that women usually seek health care assistance more frequently, not necessarily meaning that they are more affected by diseases, but, instead, that they tend to be more careful with their own wellness [64,65]. In Brazil, some studies found higher dengue notification among women [66,67], and others showed no significant sex difference [68,69]. In our data, from 2007 to 2015, 55% of patients that notified DENV cases were women while 45% were men, while the 2010 Population Census indicates that 52% of the residents in Campinas were women, and 48% were men [20].…”
Section: Discussionmentioning
confidence: 99%
“…populations, uncontrolled urbanization, population growth, climate change, and increasing numbers of international travelers. (1,2,4,5,7) In Brazil, the number of cases of dengue fever reported in January-August 2019 was approximately 600% higher than that reported during the same period in 2018. As of August 2019, the disease had caused 591 deaths, compared with only 141 for the same period in 2018.…”
Section: To the Editormentioning
confidence: 93%
“…The dengue virus (DENV) belongs to the Flaviviridae family, and humans can be infected with any of the four antigenically distinct serotypes (DENV 1-4). (1)(2)(3)(4)(5)(6)(7) The prevalence of DENV infection has increased dramatically in recent decades; the disease is now endemic in > 100 countries worldwide. The global resurgence of dengue is thought to be due to the failure to control Aedes spp.…”
Section: To the Editormentioning
confidence: 99%
“…DENV was first detected in Brazil in 1982 [12]. Since then, it has become a serious public health concern due to its high incidence in the country and association with severe dengue illnesses [13]. Co-circulation of dengue serotypes has been observed throughout Brazil [14, 15], particularly in highly populated areas of the southeastern region that includes the federal states of São Paulo, Rio de Janeiro, Minas Gerais and Espírito Santo.…”
Section: Introductionmentioning
confidence: 99%
“…Between 1995 and 2015, Brazil reported nearly 8 million DENV cases, which comprises 55% of all cases reported in the Americas during this period [12]. Over the last thirty years, the southeast region of Brazil has reported 2225 dengue-related fatal cases, representing 43% of all dengue-related deaths in the country [13].…”
Section: Introductionmentioning
confidence: 99%